2014
DOI: 10.1586/17469899.2014.917960
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines as villains and potential therapeutic targets in thyroid-associated ophthalmopathy: from bench to bedside

Abstract: Summary The pathophysiology underlying Graves’ disease and its ocular manifestation, thyroid associated ophthalmopathy (TAO) is incompletely understood. Characterization of the mononuclear cells driving the disease and the cytokines they produce has led to significant advances in our understanding of TAO. This in turn has resulted in the identification of potentially attractive drug targets. For instance, development of inhibitors of specific cytokine pathways for use in other autoimmune diseases now presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 85 publications
0
17
0
2
Order By: Relevance
“…These autoimmune diseases are regulated by the IL-23/IL-17A axis. IL-23, secreted by dendritic cells and macrophages, maintains the phenotype and function of Th17 cells [38]. Retinoic acid receptor-related orphan receptor-γt and signal transducer and activator of transcription 3 are key regulators of the transcription of il17a and the differentiation of Th17 cells.…”
Section: Cd4+ T Cellsmentioning
confidence: 99%
“…These autoimmune diseases are regulated by the IL-23/IL-17A axis. IL-23, secreted by dendritic cells and macrophages, maintains the phenotype and function of Th17 cells [38]. Retinoic acid receptor-related orphan receptor-γt and signal transducer and activator of transcription 3 are key regulators of the transcription of il17a and the differentiation of Th17 cells.…”
Section: Cd4+ T Cellsmentioning
confidence: 99%
“…Remarkably, contrary to the need for development of antigen-specific therapy for GO, an ever-growing number of non-specific immune-related and signal transduction molecules are being proposed as potential targets for therapy in GO. Indeed, one laboratory in the past 4 years has published data on the following molecules described to be of interest in this regard; IL-1R antagonist, IL-6, IL-8, IL-12, IL-23/IL-17, TNF alpha, Slit2, CXCL-12/CXCR4, Pen-traxin-3, PTEN, AIRE, PCP-1, and p53 [101][102][103][104][105][106][107][108]. The modified Bill Clinton campaign slogan mentioned above deserves repeating.…”
Section: F) Extrathyroidal Manifestations Of Graves' Diseasementioning
confidence: 99%
“…Among them, 105 were duplicated records. From the remaining 280 articles, we found 27 to be relevant according to our study criteria 1 21 22 23 24 25 26 27 28 29 31 32 33 34 35 38 39 40 41 42 43 44 45 46 47 48 49 . We further manually screened the reference lists and identified another 3 relevant studies 30 36 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 30 articles were studied. We excluded 5 reviews 1 44 47 48 49 , 3 studies in which there were no sufficient genotypic or allelic data after communication with the authors 38 45 46 , and 1 study with duplicated samples 43 . Also excluded were 5 other studies, in which the SNPs were reported only once in the literature and not eligible for meta-analysis 27 33 35 39 40 .…”
Section: Resultsmentioning
confidence: 99%